Prospects of regenerative current breaking in DC circuit breaker topology - S. M. Sanzad Lumen; Ramani Kannan; Nor Zaihar Yahaya (Institute of Advanced Engineering and Science, 2021)
Due to the stunning advancement of power electronics, DC power system is getting immense attention in the field of research. Protection and hereafter the protective devices for the DC power system application are two vital areas that need to be explored and developed further. Designing a protective device such as DC circuit breaker possesses a lot of challenges. The main challenge is to interrupt a current which does not have a natural zero crossing like AC current has. In addition, energy is stored in the network inductances during normal operation. Instantaneous current breaking is opposed by this stored energy during circuit breaker tripping, hence, all the DC circuit breaker topologies proposed in literature use snubber network, nonlinear resistor to dissipate this stored energy as heat during the current breaking operation. However, it is possible to store this energy momentarily and reuse it later by developing an improvised topology. In this paper, the prospects of energy recovery and reuse in a DC circuit breaker was studied and a new topology with regenerative current breaking capability had been proposed. This new topology can feed the stored energy of the network back into the same network after breaking the current and thus can improve the overall system efficiency.